Outcomes of Autologous Reconstruction in Comparison with Alloplastic in Microtia Patients - Dini Widiarni Widodo; Eka Dian Safitri; Mirta Hediyati Reksodiputro; Irfan Irfan (Faculty of Medicine Universitas Indonesia, 2022)
Background: Microtia is a congenital abnormality of the auricle. One of the important comprehensive management of microtia is ear reconstruction. Reconstruction using an auricle framework from autologous material originating from the rib cartilages is still the gold standard. However, currently, some surgeons prefer alloplastic materials which are claimed to reduce morbidity and can be performed at a younger age. Objective: Report a case of a microtia patient who underwent autologous reconstruction followed by a literature search comparing the outcomes of autologous and alloplastic reconstruction. Case: An 11-year-old with grade 3 unilateral microtia who underwent autologous reconstruction surgery using materials from the rib cartilages. Later he complained of pain at the rib grafting site, more than at the surgical wound in the ear. Methods: A literature search based on the clinical question was done in PubMed, EBSCOhost, Cochrane Library, and by hand searching. Results: Three relevant articles that fit the clinical question were included. Autologous reconstruction causes fewer complications, while alloplastic reconstruction is better aesthetically. Further research is needed regarding the quality of life. Conclusion: Auricular reconstruction using autologous material remains the superior material of choice. Alloplastic framework can be an alternative choice with better aesthetic results but greater complication risk.